Carotid Artery Disease - Mosley, Mary (MD Conference Express, 2015)
All patients with carotid artery disease should be treated with medical therapy that includes an antiplatelet agent, a statin, and an angiotensin-converting enzyme inhibitor or angiotensin receptor blocker. For patients with high-grade stenosis, revascularization with carotid endarterectomy or carotid artery stenting reduces stroke and cardiovascular events.